PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI PERIODE TAHUN 2014-2018 - Rizka Herrera Vianastie; Kun Ismawati; Yanita Hendarti (Economics, Social, and Humanities Journal (Esochum), 2022)
Competition in pharmaceutical companies increased. This study aims to determine the effect of liquidity, solvability, and profitability ratios on stock prices in pharmaceutical companies listed o the IDX for the period 2024-2018, pra pandemic era. This reseach is a descriptive quantitative study. The population of this study is 10 pharmaceutical companies listed on the IDX for the period 2014-2018. Nine companies met the criteria. The company registered and published financial reports periodically during the observation period. The data were tested by using the t-test, f-test, coefficient of determination test, and multiple linier regression. Research results are, 1). Liquidity as proxied by CR has no significant effect on share prices in pharmaceutical companies listed on the IDX for the period 2014-2018, 2). Solvability as proxied by DER has a significant effect on share prices in pharmaceutical companies listed on the IDX for the period 2014-2018, 3). Profitability as proxied by ROA has a significant effect on share prices in pharmaceutical companies listed on the IDX for the period 2014-2018, 4). CR, DER. and ROA simultaneously have significant effect on stock price in pharmaceutical companies listed on the IDX for the period 2014-2018. Implications of this study are: more solvable and more profitable the company, raises their share price. It needs management’s ability to maintain DER and ROA fot a better result on share prices.